Assessment of Climate Change Over the Indian Region 2020
DOI: 10.1007/978-981-15-4327-2_2
|View full text |Cite|
|
Sign up to set email alerts
|

Temperature Changes in India

Abstract: Key Messages • Annual mean, maximum and minimum temperatures averaged over India during 1986-2015 show significant warming trend of 0.15°C, 0.15°C and 0.13°C per decade, respectively (high confidence), which is consistent with dendroclimatic studies. • Pre-monsoon temperatures displayed the highest warming trend followed by post-monsoon and monsoon seasons. • The frequency of warm extremes over India has increased during 1951-2015, with accelerated warming trends during the recent 30 year period 1986-2015 (hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 80 publications
(103 reference statements)
2
15
0
Order By: Relevance
“…In general, over twice of the global land area, the daytime T s has been increasing at a lower rate than the nighttime T s (Cox et al 2020), thereby suppressing the diurnal temperature range (Kothawale and Rupa Kumar 2005). Recently, Sanjay et al (2020) have observed that annual mean, maximum and minimum temperatures averaged over India as a whole show significant warming trends of 0.15 °C, 0.15 °C, and 0.13 °C per decade, respectively, since 1986.…”
Section: Introductionmentioning
confidence: 99%
“…In general, over twice of the global land area, the daytime T s has been increasing at a lower rate than the nighttime T s (Cox et al 2020), thereby suppressing the diurnal temperature range (Kothawale and Rupa Kumar 2005). Recently, Sanjay et al (2020) have observed that annual mean, maximum and minimum temperatures averaged over India as a whole show significant warming trends of 0.15 °C, 0.15 °C, and 0.13 °C per decade, respectively, since 1986.…”
Section: Introductionmentioning
confidence: 99%
“…High altitude and decrease of temperature as per normal and adiabatic lapse rate, expansion of airmass in high altitude is the main cause behind CW occurrences in J & K and its adjoining areas. The spatial extent of CW susceptibility and its intensity was found maximum during the winter season due to the winter solstice caused by the southern migration of sun and oblique sun rays in the Northern part of India, particularly in this part located in relatively higher northern latitude (Sanjay et al, 2020). Now, why CW consistency and intensity was found high in north-western and central India particularly Rajasthan, Delhi, and adjoining parts?…”
Section: Grid-specific Trend Of Hw and Cw Frequencymentioning
confidence: 99%
“…There is particular variance in the climate changes between the northern and southern parts of the country, with both becoming increasingly warmer over historic meteorological trends (Dash and Hunt, 2007). At the base of the Himalayas, surface temperatures extremes are increasing: hotter in the summer months and colder in the winter (Dash and Hunt, 2007; Dash et al ., 2007; Sanjay et al ., 2020). Monsoon precipitation increasingly fluctuates, predicted to increase across India into the near future; monsoon rains also tend to start earlier as a result of anthropogenic aerosols (Bollasina, Ming and Ramaswamy, 2013; Kulkarni et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%